Xenophobia in urban spaces: Analyzing the drivers and social justice goals from the Ugandan-Asian debacle of 1972 and xenophobic attacks in South Africa (2008-2019) - Sempijja, Norman; Mongale, Collin Olebogeng (Frontiers in Sustainable Cities, 2022)
Xenophobic attacks have long been prevalent in post-independence Africa, as shown by the expulsion of Ugandans of Asian origin from Uganda in 1972. Post-apartheid South Africa has experienced continuous xenophobic attacks on Africans since 2008. In both cases the attacks were not framed as xenophobic by the state. Instead, they were framed within a socio-economic context, where the targeted groups were criminalized and securitised by the general population. The goal of this qualitative study is to analyse the drivers and social justice goals of xenophobia in urban spaces. This is done by looking into case studies of the 1972 Ugandan-Asian expulsion in Uganda, and the xenophobic attacks on foreigners in South Africa (2008–2019). The case studies provide key debates surrounding the drivers and social justice goals of xenophobic attacks in both Uganda and South Africa. The paper thus examines the relative deprivation in both countries, which assists in explaining the onset of the xenophobic attacks. Findings are that although the Ugandan-Asian debacle and xenophobic attacks in South Africa were triggered by drivers such as income inequality, inter-group hatred, racism, poverty, unemployment and competition for resources, the quest for social justice emanating from historical socio-economic grievances was deeply entrenched in both cases. Yet the paper further argues that rather than addressing social injustice, xenophobia perpetuates it by creating new victims and shielding the governments from the spotlight on their failings especially in addressing poverty, inequality, and overall access to economic opportunities to mention but a few. The paper recommends a need for political will to tackle xenophobia and the socio-economic challenges and a need for community dialogue and inter-community linkages crucial when dealing with grievances.